(untitled) (World Bulletin of Social Sciences, 2023)
It is known that disorders of the functional state of the liver in chronic diseases initiate hemostatic disorders that predispose to the manifestation of bleeding. In patients with chronic hepatitis B, disorders of the hemostasis system are observed mainly in the form of disseminated intravascular coagulation, the outcomes, stage and severity of which depend on the degree of invasiveness of endothelial cells and liver fibrosis.